Prognosis and complete remission rate of diffuse large B‐cell lymphoma patients in standard R‐CHOP with reduction of vincristine: A retrospective study - Riasi, Fatemeh; Ataei Azimi, Sajjad; Allahyari, Abolghasem; Moeini Nodeh, Mohammad; Shakeri, Mohammad T.; Kamandi, Mostafa (Health science reports, 2023)
Background and Aims The effect of stopping or reducing the dose of vincristine in diffuse large B‐cell lymphoma (DLBCL) on the outcome and prognosis of the disease is still in doubt. The present study aimed to investigate and compare the prognosis and complete remission of two R‐CHOP treatment regimens with and without vincristine reduction in DLBCL patients. Methods This retrospective study was conducted on newly diagnosed DLBCL patients during 2018–2021. The patients were over 18 years of age, had been histologically confirmed by a pathologist, and were under treatment with R‐CHOP regimen. The clinical information of the subjects as well as the number of treatment courses were extracted from their medical records and then compared. Results Overall, 269 patients with DLBCL were included in this study, 15.99% of whom (n = 43) had vincristine reduction. There was no significant difference between the studied factors regarding the reduction of vincristine and the complete R‐CHOP regimen (p > 0.05). Besides, no difference was observed in the 1‐year overall survival (OS) and progression‐free survival (PFS) of the patients in the two groups treated with R‐CHOP regimen with and without vincristine reduction (p > 0.05). The complete remission rates of the patients treated with R‐CHOP regimen with and without vincristine (p > 0.05) were not different either. The results of the Cox multivariate regression showed that reducing the dose of vincristine from the R‐CHOP treatment regimen had no relationship with the 1‐year OS and PFS of the DLBCL patients (hazard ratio [HR]OS = 1.59, 95% confidence interval [CI]: 3.67–0.690, HRPFS = 1.67, 95% CI: 0.798–3.82). Conclusion The results of this study showed that the reduction of vincristine from the R‐CHOP regimen in the DLBCL patients was not likely to make a difference in the 1‐year OS and PFS of the patients. However, further studies are needed on the issue.